In vitro anti-malarial interaction and gametocytocidal activity of cryptolepine - Forkuo, Arnold Donkor (Malar J, 2017)
BACKGROUND: Discovery of novel gametocytocidal molecules is a major pharmacological strategy in the elimination and eradication of malaria. The high patronage of the aqueous root extract of the popular West African anti-malarial plant Cryptolepis sanguinolenta (Periplocaceae) in traditional and hospital settings in Ghana has directed this study investigating the gametocytocidal activity of the plant and its major alkaloid, cryptolepine. This study also investigates the anti-malarial interaction of cryptolepine with standard anti-malarials, as the search for new anti-malarial combinations continues. METHODS: The resazurin-based assay was employed in evaluating the gametocytocidal properties of C. sanguinolenta and cryptolepine against the late stage (IV/V) gametocytes of Plasmodium falciparum (NF54). A fixed ratio method based on the SYBR Green I fluorescence-based assay was used to build isobolograms from a combination of cryptolepine with four standard anti-malarial drugs in vitro using the chloroquine sensitive strain 3D7. RESULTS: Cryptolepis sanguinolenta (IC(50) = 49.65 nM) and its major alkaloid, cryptolepine (IC(50) = 1965 nM), showed high inhibitory activity against the late stage gametocytes of P. falciparum (NF54). In the interaction assays in asexual stage, cryptolepine showed an additive effect with both lumefantrine and chloroquine with mean ΣFIC(50)s of 1.017 ± 0.06 and 1.465 ± 0.17, respectively. Cryptolepine combination with amodiaquine at therapeutically relevant concentration ratios showed a synergistic effect (mean ΣFIC(50) = 0.287 ± 0.10) whereas an antagonistic activity (mean ΣFIC(50) = 4.182 ± 0.99) was seen with mefloquine. CONCLUSIONS: The findings of this study shed light on the high gametocytocidal properties of C. sanguinolenta and cryptolepine attributing their potent anti-malarial activity mainly to their effect on both the sexual and asexual stages of the parasite. Amodiaquine is a potential drug partner for cryptolepine in the development of novel fixed dose combinations.